P113 Advanced clinical practitioner (ACP) hot airways clinic: a 12 month feasibility study. (11th November 2022) - Bradley, ER; Baron, R; Brij, SO; Khan, WA
Abstract : Background: Following COVID restrictions for aerosol-generating procedures, spirometry provision both in primary and secondary care has been reduced. Out-patient referrals to clarify airways disease diagnosis increased 205% since 2019. Subsequently, waiting times for out-patient Consultant review with diagnostics were in excess of 16 weeks. Thus, a HOT Airways Clinic led by a non-Consultant grade was devised and implemented. Objectives: 1) Facilitate rapid specialist assessment for diagnosis/management of airways disease. 2) Provide patient-centred management plans encompassing pharmaceutical, psychosocial and behavioural therapies. 3) Ensure appropriate follow-up. Methods: Referral criteria for an ACP-led Airways Clinic were agreed (aged over 18; no need for admission; airways disease confirmed or suspected as the primary problem; emergency care provided). Clinics were performed weekly with dedicated access to spirometry (FEV1; FVC; PEFR; reversibility studies and FeNO) as well as and other diagnostics (blood testing and radiology) to facilitate standard care. Results: 102 patient referrals were reviewed: median age 51 years (IQR 36–60); female 49%; BAME 32%; baseline FEV1 63% predicted; current smokers 38%). Referral source: 62% from urgent care; 18% GP referrals; 18% Airways Team and 3% from other Respiratory Consultants. Average waiting time from referral to appointment 2 weeks (range 2–39 days). Referral question: diagnosis 64 (62%); disease optimisation 38 (37%). Of those reviewed a definitive diagnosis was made in 60% (n=50); 40% (n=34) had treatment optimisation with 17% (n=18) non-attendance. Key interventions included: health promotion (smoking cessation referral was offered to all smokers and accepted in 78% of cases); medication education (92%); spirometry and/or full lung function (64%); CT scanning (31%) and novel pharmaceutical intervention (72%). Most patients had 2 out-patient attendances (range 1–4) in the clinic. Patient satisfaction was favourable: very satisfied 72% (n=62) or satisfied 29% (n=23). Conclusion: The ACP-led HOT Airways Clinic has been commissioned and will continue as an integral part of the Airways Clinical Pathway. The ACP-led HOT Airways Clinic is timely and cost-effective with a significant reduction in time taken for diagnostics and onward Consultant referrals.